Improvement on the fabrication of SiC materials: Processing, reinforcing phase, fabricating route—A review - S.D. Oguntuyi; K. Nyembwe; M.B. Shongwe; O.T. Johnson; J.R. Adewumi; N. Malatji; P.A. Olubambi (International Journal of Lightweight Materials and Manufacture, 2023)
Abstracts: The ceaseless exploration for the improvement of ceramic materials has created a lot of techniques, all aimed at producing ceramic materials that can withstand environmental conditions and other factors. Most of thecommon techniques have their advantages and drawbacks. Some of the techniques involve the addition of a reinforcing phase to monolithic ceramic, the application of diverse sintering routes for the fabrication of ceramic products, and the preparatory methods for producing powder materials which cannot be jettisoned. These processes have been evaluated to influence the final ceramic products. Undoped/monolithic/single-phase ceramic has had some limitations in its processing, densification, and mechanical properties limiting its wide application in all circumstances. Hence, the incorporation of reinforcing phase, which can sometimes be called the secondary phase in the ceramic matrix, has significantly evolved into one of the possible means to nullify these challenges posed by undoped ceramics. This review consciously highlights and pinpoints all routes that have been taken to improve the properties of undoped SiC via the introduction of reinforcing phase, processing techniques, sintering techniques, etc. Finally, the possible prospects for future directions, advancement, and opportunities in the production of ceramic materials are concluded.